Chronic pancreatitis: an international draft consensus proposal for a new mechanistic definition - Whitcomb, David C.; Schneider, Alexander (Pancreatology, 2016)
Background - A definition of chronic pancreatitis (CP) is needed for diagnosis and distinguishing CP from other disorders. Previous definitions focused on morphology. Advances in epidemiology, genetics, molecular biology, modeling and other disciplines provide new insights into pathogenesis of CP, and allow CP to be better defined. - Methods - Expert physician-scientists from the United States, India, Europe and Japan reviewed medical and scientific literature and clinical experiences. Competing views and approaches were debated until a new consensus definition was reached. - Results - CP has been defined as ‘a continuing inflammatory disease of the pancreas, characterized by irreversible morphological change, and typically causing pain and/or permanent loss of function’. Focusing on abnormal morphology makes early diagnosis challenging and excludes inflammation without fibrosis, atrophy, endocrine and exocrine dysfunction, pain syndromes and metaplasia. A new mechanistic definition is proposed - ‘Chronic pancreatitis is a pathologic fibro-inflammatory syndrome of the pancreas in individuals with genetic, environmental and/or other risk factors who develop persistent pathologic responses to parenchymal injury or stress.’ In addition, “Common features of established and advanced CP include pancreatic atrophy, fibrosis, pain syndromes, duct distortion and strictures, calcifications, pancreatic exocrine dysfunction, pancreatic endocrine dysfunction and dysplasia.” This definition recognizes the complex nature of CP, separates risk factors from disease activity markers and disease endpoints, and allows for a rational approach to early diagnosis, classification and prognosis. - Conclusions - Initial agreement on a mechanistic definition of CP has been reached. This definition should be debated in rebuttals and endorsements, among experts and pancreatic societies until international consensus is reached.
Gesehen am 28.03.2019